2010
DOI: 10.1038/onc.2010.479
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory cytokines hepatocyte growth factor and interleukin-11 are over-expressed in Polycythemia vera and contribute to the growth of clonal erythroblasts independently of JAK2V617F

Abstract: The V617F activating mutation of janus kinase 2 (JAK2), a kinase essential for cytokine signalling, characterizes Polycythemia vera (PV), one of the myeloproliferative neoplasms (MPN). However, not all MPNs carry mutations of JAK2, and in JAK2-mutated patients, expression of JAK2V617F does not always result in clone expansion. In the present study, we provide evidence that inflammation-linked cytokines are required for the growth of JAK2V617F-mutated erythroid progenitors. In a first series of experiments, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 53 publications
4
58
0
Order By: Relevance
“…There is proof of yet unexplained JAK2V617F-independent cytokine over-production in MPN, by both bone marrow stromal cells and malignant hematopoietic progenitors. 19,20 The cytokines that were found to be over-produced were all linked to inflammation as well as capable of stimulating myelopoiesis, an unsurprising finding since evidence of inflammation in MPN is abundant. 21 Future studies investigating the possible expression and consequences of INSL6 and INLS4 expression in cell types relevant to myelopoiesis and their relationship to the 46/1 status of patients should bring new and important insights into the pathogenesis of myeloid neoplasms as well as of inflammatory diseases.…”
mentioning
confidence: 99%
“…There is proof of yet unexplained JAK2V617F-independent cytokine over-production in MPN, by both bone marrow stromal cells and malignant hematopoietic progenitors. 19,20 The cytokines that were found to be over-produced were all linked to inflammation as well as capable of stimulating myelopoiesis, an unsurprising finding since evidence of inflammation in MPN is abundant. 21 Future studies investigating the possible expression and consequences of INSL6 and INLS4 expression in cell types relevant to myelopoiesis and their relationship to the 46/1 status of patients should bring new and important insights into the pathogenesis of myeloid neoplasms as well as of inflammatory diseases.…”
mentioning
confidence: 99%
“…3 These cytokines affect marrow mesenchymal cells that are not involved by the malignant process. [3][4][5][6][7][8][9] Recently, neutrophil gelatinase-associated lipocalin (lipocalin-2; LCN2) has been implicated in the pathobiology of myeloproliferative neoplasms (MPNs). [10][11][12][13] LCN2 promotes the proliferation of the malignant clone in chronic myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Two separate studies have suggested a functional role for HGF/MET in PV 22, 23 , and a previous exome sequencing study of MPN patient samples identified acquired mutations in MET (V1247A, adjacent to the somatic mutation identified in our screen) and in ERBB2 (L494F) 24 . Overall, mutations in ERBB receptors, MET and ALK are rare in MPN (those described to date are summarized in Suppl.…”
Section: Resultsmentioning
confidence: 62%